A tutorial on discourse analysis in healthy and pathological ageing - Varela Suárez, Ana (International Journal of Language and Communication Disorders, 2023)
Background: Age is a key factor when dealing with language and speech disorders, as it entails a progressive loss of neuroplasticity even in healthy individuals. Apart from this, ageing also affects our word-retrieval abilities, and thus, our discursive skills, particularly in people suffering from neurodegenerative diseases. Therefore, descriptions and/or measures of communicative performance always need to be interpreted through the lens of variation across the lifespan. Aim: This paper's main objective is to create a general tutorial for researchers willing to start delving into discourse analysis, both in healthy and pathological ageing. Methods: An eight-step tutorial on discourse analysis in the elderly is presented. Each of these steps starts with general recommendations and progresses to more specific topics that may be relevant when conducting this type of research. All of the steps have been extrapolated from an extensive literature review on discourse analysis. Main Contributions: This work presents an easy-to-follow, step-by-step tutorial on discourse analysis in the elderly. It is aimed at clinical researchers who are taking their first steps in discourse analysis.It may also be useful for those who are already familiar with the methodology but may be interested in reading a general overview on the topic. Moreover, it offers new insights into the following topics: types of research questions, advantages and disadvantages of the different research methodologies and ethical considerations for data production in clinical linguistics. Conclusions: Discourse analysis in the elderly is a highly complex issue that may require researching from different approaches and disciplines. This implies following a well-planned and thorough process, which we have detailed through the following eight steps: (i) reviewing literature; (ii) formulating the research question; (iii) designing the study; (iv) producing data; (v) selecting technological tools for data treatment; (vi) transcribing the corpus; (vii) annotating the corpus and (viii) analysing and interpreting the results. What This Paper Adds: What is already known on the subject Approaches in discourse analysis in elderly adults, and particularly, in people suffering from dementia have already been analysed by previous researchers and categorised into three main trends: the quantitative-experimental approach, the qualitative-naturalistic approach and an in-between path, the quantitative-naturalistic approach. Also, several handbooks on general discourse analysis have presented comprehensive revisions on potential resources and methodologies that can be applied to researching discourse in elderly populations. What this paper adds to existing knowledge This paper takes these three main approaches and analyses how the most recent research on language in ageing and dementia fits into them. Furthermore, it reviews the advantages and disadvantages each of them may bring for beginners in the field of discourse analysis. Moreover, it adds some studies that may fit into a fourth approach: the qualitative-experimental. This article also presents information about several of the main steps when analysing data from the pragmatic perspective: the formulation of the research question, data production and the transcription/annotation process. What are the potential or actual clinical implications of this work? This work has been devised for linguists who may want to read a systematization of the steps for analysing discourse in elderly populations. It may also be of interest to specialists from different fields such as speech therapy, psychology, gerontology or neurology who desire to start applying methods from discourse analysis in their work and aim to have a comprehensive scope of the main research trends within the field of clinical pragmatics.
Keywords: Alzheimer's disease; clinical pragmatics; dementia; discourse analysis; elderly adults; methodology; JCR; Scopus